Does granulocyte-macrophage colony-stimulating factor prevent bacterial translocation in rats with surgical trauma and obstructive jaundice? - Ali E. DEMİRAĞ,; Nesrin TURHAN,; Serpil ERCİS,; Erhan HAMALOĞLU, (Turkish Journal of Gastroenterology, 2019)
-